Analisis Volume, Kecepatan Lalu Lintas Dan Tingkat Kebisingan Akibat Lalu Lintas Pada SDN 1 Angsau - Septia Rona Puspita Gaby Tia (Universitas Bojonegoro, 2026)
The development of transportation activities in Pelaihari District has led to an increase in vehicle volume that has the potential to cause noise, especially in educational areas. Angsau 1 Public Elementary School is a school located near Jalan Parit Baru, making it at risk of being affected by traffic noise. This study aims to analyze the relationship between traffic volume and speed and noise levels, calculate noise levels using the Calculation of Road Traffic Noise (CoRTN) method, compare the results with noise quality standards, and provide recommendations for noise control. The study used a quantitative descriptive method with data collection on Fridays and Saturdays at 08.00–10.00 WITA and 13.00–15.00 WITA at three observation points located 15 m, 25 m, and 35 m from the noise source. Data collected included traffic volume, vehicle speed, and noise levels using a Sound Level Meter (SLM). The results showed that traffic volume ranged from 851–1,105 vehicles/hour with an average speed of 35.75–37.45 km/hour. The noise level from direct measurements ranged from 72.4 to 82.0 dB(A), while the calculated results from the CoRTN method ranged from 53.3 to 62.4 dB(A). Regression analysis showed that increasing traffic volume tended to increase noise levels, while vehicle speed showed an inverse relationship. Most of the measurement results exceeded the school area noise quality standard of 55 dB(A). Noise control is recommended through building insulation, the use of sound-absorbing materials, traffic management, and the addition of vegetation as a natural barrier.